Revascularization in Immature Permanent Teeth - A Case Series - C Jose, Sherin; Mathew, Joel; Elizabeth Mathews, Sneha (Journal of Nepalese Association of Pediatric Dentistry, 2023)
Immature permanent teeth with developing, root apices with dental pulp infections resulting from caries or trauma represent a formidable clinical challenge. Biologically based principles of regenerative endodontic procedures in the treatment of immature, necrotic teeth have replaced the traditional ‘apexification’ procedures. The purpose of this case series was to investigate the outcome of the pulpal revascularization procedure on immature permanent teeth with or without apical periodontitis. The case series comprised 3 patients (8–11 years of age), consisting of 4 incisors and 1 premolar with incompletely formed apex with or without signs or symptoms of periapical pathology. Induction of blood clot was the technique selected for root closure if the tooth was asymptomatic following the placement of intracanal antibiotic paste for 3 weeks. Apexification was initiated if the tooth remains symptomatic. Out of the five teeth revascularisation was successful, and continued root-end closure was obtained in four teeth. One tooth remained symptomatic and apexification was initiated. One patient failed to follow up for the study. Revascularisation by induction of apical bleeding is a potential source of stem cells for the continued root maturation and it creates a blood clot that would act as a biologic scaffold for the recruited stem cells.